1995
DOI: 10.1159/000276757
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Clinical Outcome of Neurogenic Tumours in the Head and Neck Area

Abstract: A retrospective analysis of diagnostic procedures and clinical outcome of patients with neurogenic tumours of the head and neck region was performed. There were 25 patients – 16 with neurinoma, 5 with neurofibroma and 4 with neurogenic sarcoma – who presented with a mass in the head and neck area. In 13 patients, the neurinoma originated from the facial nerve, 2 of them were located in the middle ear and mastoid and showed facial palsy. Four patients presented with neurofibromatosis type 1. Twenty-three patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Neurofibromas may occur in isolation or as a part of Von Recklinghausen's syndrome in combination with café au lait skin patches, lisch's nodules, axillary freckling and fibroma molluscum [2]. The disease may be inherited as an autosomal dominant trait with variable penetrance in 50% of patients or it may occur as a result of spontaneous mutation [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurofibromas may occur in isolation or as a part of Von Recklinghausen's syndrome in combination with café au lait skin patches, lisch's nodules, axillary freckling and fibroma molluscum [2]. The disease may be inherited as an autosomal dominant trait with variable penetrance in 50% of patients or it may occur as a result of spontaneous mutation [3].…”
Section: Discussionmentioning
confidence: 99%
“…Most tumours caused by NF need no treatment, but tumours that are painful, disfiguring, growing rapidly or impairing function need treatment. In main trunk neurofibroma, nerve autografting with interposition is therapy of choice with good chance of functional recuperation [3]. Large lesion may require reconstruction and elevation of pinna with dermal strips or marlex mesh [4].…”
Section: Discussionmentioning
confidence: 99%
“…The nerve of origin cannot be identified without surgical exploration [1,[4][5][6][11][12][13]. Ultrasonography permits direct visualization of the vagus nerve, distinction between schwannomas of the cervical sympathetic chain and schwannomas of the vagus nerve and a relationship to surrounding blood vessels [11]. In our patient the history of pain and the topography of the lesions (using CT and MRI) suggested that the auriculotemporal nerve was the nerve of origin but definitive assessment only was provided by surgical exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Radical resection is only indicated if there is certainty that no motor nerves (such as the facial nerve) are affected, as reconstruction of significant motor nerves may produce incomplete functional recovery [11,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation